Thermoeconomic analysis of a waste heat recovery system with fluctuating flue gas scenario. (1st November 2022) - Hsieh, Jui-Ching; Lai, Chun-Chieh; Chen, Yen-Hsun
Abstract: The performance and economy of a waste heat recovery system featuring a fin tube heat exchanger (FTHE) and an organic Rankine cycle system with a fluctuating flue gas were investigated. The output power of this system increased with the temperature and mass flow rate of the flue gas ( m ˙ f ), which had positive and negative effects, respectively, on the effectiveness ( ε FT ) of the FTHE. Furthermore, ε FT increased with the evaporation temperature ( T eva ). The system performance and economy can be increased and decreased, respectively, through an increase in T eva, especially for as the m ˙ f less than the design conditions. A method in which the flow rate of the working fluid is restricted through adjustment of the rotation speed of the expander is proposed to reduce the heat absorbed by the evaporator when the evaporation temperature increases. At a low evaporation heat transfer rate, when the rotation speed of the expander decreased from 1350 to 900 rpm, the evaporation pressure increased from 1.36 to 1.77 MPa, and system efficiency and output power increased by 1.0% and 204.7 W, respectively. Finally, results of the experiment confirmed that increasing evaporation pressure can increase system performance under low heat transfer rate. Highlights: Performance and economy of a WHRS in a fluctuating flue are investigated. The WHRS is composed of a FTHE, ORC and cooling source. Flow rate and temperature of flue have negative and positive effect on effectiveness, respectively. Increasing evaporation temperature improves performance under low flow rate. Improving performance method in theoretical results confirmed by the experimental ORC.